2010
DOI: 10.1111/j.1365-2699.2009.02253.x
|View full text |Cite
|
Sign up to set email alerts
|

Parapatric diversification after post‐glacial range expansion in the gall flyUrophora cardui(Tephritidae)

Abstract: Aim  Primary and secondary genetic clines in post‐glacial colonized regions have different implications for biogeographic distributions and the origin of species. Primary clines arise in situ after colonization as adaptive responses to environmental gradients, while secondary clines are caused by contact between vicariant lineages. Here we analyse primary versus secondary origin of a genetic cline in the tephritid fly Urophora cardui in Jutland, Denmark, in a post‐glacial landscape. Location  Western Palaearct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
(114 reference statements)
0
7
0
Order By: Relevance
“…DI in U. cardui was found in geographically and genetically separated populations with different intrataxon strains. As the phylogeographic differentiation in U. cardui is found both for mtDNA and nuclear genes (Johannesen et al, 2010), the present study provides evidence for sustained DI in U. cardui that is older than the current geographic distribution of the fly and which is not related to a selective sweep of infected mitochondrial haplotypes (Hurst & Jiggins, 2005). The genetic transition zone in U. cardui, which is defined by allelic variation of AAT, was not related to Wolbachia AAT.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…DI in U. cardui was found in geographically and genetically separated populations with different intrataxon strains. As the phylogeographic differentiation in U. cardui is found both for mtDNA and nuclear genes (Johannesen et al, 2010), the present study provides evidence for sustained DI in U. cardui that is older than the current geographic distribution of the fly and which is not related to a selective sweep of infected mitochondrial haplotypes (Hurst & Jiggins, 2005). The genetic transition zone in U. cardui, which is defined by allelic variation of AAT, was not related to Wolbachia AAT.…”
Section: Discussionmentioning
confidence: 44%
“…Analysis was performed near exclusively on adults, N = 508 adults + 12 larvae = 520 specimens, with the purpose of avoiding the potential bias of parasitoid encapsulation in larvae that might impact estimates of infection. The frequency of single infections (SI) and double infections was compared among regional populations previously identified (Johannesen et al, 2010;Steinmetz et al, 2004) U. stylata and its specialist endoparasitoid E. compressa F. and its associated E. robusta were screened from individuals collected in Denmark and Germany in 2014 (Appendix S1). The endoparasitoids E. serratulae and E. compressa were analyzed as adults and treated as described above for U. cardui, whereas the three ectoparasitoid species were analyzed as both adults and larvae.…”
Section: Handling and Geographic Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The study, based on allozyme loci, identified non-concordant clines at three loci and no clines at another four. Johannesen, Drüeke & Seitz (2010) reported dominance of the same mtDNA haplotype on both sides of the transition zone that belonged to a Western European lineage experiencing population expansion. This mix of allelic distributions across the transition area suggested an in situ origin of the parapatric divergence rather than one caused by secondary contact of two allopatrically evolved populations, i.e., by vicariance.…”
Section: Introductionmentioning
confidence: 98%
“…Urophora cardui L. (Diptera: Tephritidae) is a specialist gall maker associated with creeping thistle Cirsium arvense (L.) Scop (Asteraceae). Initially attracting attention as a biological control agent of C. arvense in Canada ( Zwölfer, Englert & Pattullo, 1970 ; Peschken & Harris, 1975 ), U. cardui has since been studied for a range of topics in its native Western Palearctic and introduced Canadian distribution ranges: biogeography, evolution of galls, interactions with parasitoids and for pest control (e.g., Peschken & Harris, 1975 ; Zwölfer, 1979 ; Eber & Brandl, 1997 ; Johannesen, Drüeke & Seitz, 2010 ; De Clerck-Floate & Cárcamo, 2011 ).…”
Section: Introductionmentioning
confidence: 99%